2016
DOI: 10.1002/ejic.201501470
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Mediated C–H Activation and Functionalization: The Role of Poly(pyrazolyl)borate and Poly(pyrazolyl)alkane Ligands

Abstract: The emergence of hydridotris(pyrazolyl)borate (Tp) and related ligands has had a substantial influence in the field of organometallic chemistry with regards to C-H activation. The electronic and structural properties of Tp and related ligands, such as poly(pyrazolyl)alkane ligands, play an important role in [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 168 publications
(244 reference statements)
4
38
1
Order By: Relevance
“…24 In the context of the theoretical shifts we have repeated this work. The 1 H (Figure SI10) and 13 C NMR (Figure SI12) spectra near room temperature show the mean signals of rapid spin interconversion. The temperature series of the Tp2Fe proton shifts was calculated theoretically for the pure S = 2 state and measured experimentally (Figure 6).…”
Section: Theoretical and Computational Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In the context of the theoretical shifts we have repeated this work. The 1 H (Figure SI10) and 13 C NMR (Figure SI12) spectra near room temperature show the mean signals of rapid spin interconversion. The temperature series of the Tp2Fe proton shifts was calculated theoretically for the pure S = 2 state and measured experimentally (Figure 6).…”
Section: Theoretical and Computational Backgroundmentioning
confidence: 99%
“…magnets. 10,11,12 Other promising application fields of pyrazolylborate complexes are catalysis 13,14,15,16,17 and the incorporation into polymers, 18 dendrimers, 19 molecular machines, 20 and metal-organic frameworks. 21 From the very first, these compounds have been studied by using paramagnetic NMR spectroscopy (pNMR) 1,22,23,24 and the initial results have been compiled.…”
mentioning
confidence: 99%
“…Over the years, Tp x -metal complexes have been used in many catalytic transformations, [4] including the more testing functionalization of unreactive CÀHb onds. [5] These ligands have also been used to synthesize model complexes that mimic the active sites of somem etalloenzymes, [6] and to generate materials with interesting magnetic properties. [7] In the field of catalysis, andi nl ine with one of the main goals of modern synthetic chemistryf ocused on ah ighl evel of sustainability,t he recovery of the catalysta nd its reuse after each cycle still constitute am ajor challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it has been shown that there is no systematic trend in comparative electron donor ability of Tp relative to Cp [39]. Their electron-donating abilities are dependent upon the identity and oxidation state of the metal center as well as the properties of the other ligands in the complex [40].…”
Section: Introductionmentioning
confidence: 99%